Analisis Nilai Kerja Mahasiswa Akomodasi Perhotelan pada Pelaksanaan PKL (Praktik Kerja Lapangan) di Hotel - Nuriah, Iklin; Doriza, Shinta; Hamiyati (Family Welfare Education, 2023)
Work value is a goal that a person wants to achieve through his work or as a consequence of his work. Preliminary study of the students internship experience, there are differences of opinion between students and field supervisors about the work value that students have. So it is necessary to investigate the truth so that there is no misunderstanding. This study aims to identify and analyze the work value of S1 Family Welfare Education students concentrating on hotel accommodation at Jakarta State University with active student informants class of 2019 who have carried out internship experience. This study uses a type of qualitative research with a phenomenological approach. Data collection techniques were carried out by interviews, documentation and indirect observation. The process of data analysis to data visualization was carried out using the Nvivo 12 plus software. The intrinsic work value that is of concern to the findings of this study is the intellectual stimulation of students in solving problems in students whose work in 4-star hotels are more often applied than students who are work in 5-star hotels. The extrinsic work value that is of concern to the findings of this study is the work environment which is good physically, is mostly found in the experience of student work in 5-star hotels, while the work environment psychologically, in 4-star hotels and 5-star hotels that students get or feel is fairly good.